Strategic Directions of Innovative and Economic Development of the Pskov Region - M. V. Miroslavskaya (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The modern development of the economy of the Russian Federation is characterized by an imbalance in the socio-economic development of the regions, which is due to the increased interregional competition, uneven resource provision, investment history, etc. Regions are components of the unified socio-economic and political system of Russia, but each of them has its specifics. Among the factors that determine the specifics of the region stand out: historical, climatic, national, social, and economic. Taking into account all these factors, the choice of means and methods of effective management of the socio-economic system of the region should be made to ensure its sustainable long-term development and functioning. In recent years, under the influence of a qualitatively different level of development of the productive forces, the introduction of innovations in all spheres of life, IT and telecommunication systems, as well as the development of network forms of organizing production, the problem has taken on new forms.